2023
DOI: 10.1111/scd.12821
|View full text |Cite
|
Sign up to set email alerts
|

Powered or manual toothbrushing for people with physical or intellectual disabilities – A systematic review

Abstract: AimsThe aim of this systematic review is to compare the effectiveness of a powered (PTB) and a manual (MTB) toothbrush in the hands of people with physical (PD) or intellectual (ID) disabilities or in the hands of a caregiver on parameters of plaque and gingival inflammation.MethodsMEDLINE‐PubMed, Cochrane‐CENTRAL and EMBASE databases were searched from initiation up to February 2022. The inclusion criteria were clinical trials conducted in people with PDs or IDs and comparing the effect of toothbrushing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…31 On the contrary, another review published in 2022 elucidated that PTBs, in comparison with MTBs in people with physical or intellectual disabilities, resulted in no significant differences in plaque and gingival scores. 32 The antithetical evidence in different sub-populations recondites the information and makes it subject to production as well as a compilation of more robust evidence in individual sub-groups. The supremacy of PTBs as compared to MTBs in the hands of older individuals still needs to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 On the contrary, another review published in 2022 elucidated that PTBs, in comparison with MTBs in people with physical or intellectual disabilities, resulted in no significant differences in plaque and gingival scores. 32 The antithetical evidence in different sub-populations recondites the information and makes it subject to production as well as a compilation of more robust evidence in individual sub-groups. The supremacy of PTBs as compared to MTBs in the hands of older individuals still needs to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…A 2014 update of the Cochrane review of randomized controlled trials comparing PTBs and MTBs for maintaining oral health in children and adult subjects revealed that PTBs reduce plaque and gingival scores greater than MTBs in the short and long term 31 . On the contrary, another review published in 2022 elucidated that PTBs, in comparison with MTBs in people with physical or intellectual disabilities, resulted in no significant differences in plaque and gingival scores 32 . The antithetical evidence in different sub‐populations recondites the information and makes it subject to production as well as a compilation of more robust evidence in individual sub‐groups.…”
Section: Discussionmentioning
confidence: 99%